2013
DOI: 10.1128/aem.03551-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants for Cadmium and Arsenic Resistance among Listeria monocytogenes Serotype 4b Isolates from Sporadic Human Listeriosis Patients

Abstract: cIn Listeria monocytogenes serotype 4b isolates from sporadic listeriosis, heavy metal resistance was primarily encountered in certain clonal groups (ECI, ECII, and ECIa). All arsenic-resistant isolates harbored the arsenic resistance cassette previously identified in pLI100; ECIa harbored additional arsenic resistance genes and a novel cadmium resistance determinant in a conserved chromosomal locus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 39 publications
4
59
0
Order By: Relevance
“…L. monocytogenes strain F8027 (hereafter F8027) was originally derived from fresh celery and has been used as model in studies for produce colonization by L. monocytogenes (21). It grew at 35 but not at 50 g/ml cadmium chloride, hence its MIC (50 g/ml) is below the 70 g/ml threshold for resistance used in previous studies (11,12,22). PCR with previously described primers (8) indicated that F8027 was negative for previously identified cadmium resistance determinants cadA1, cadA2, and cadA3 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…L. monocytogenes strain F8027 (hereafter F8027) was originally derived from fresh celery and has been used as model in studies for produce colonization by L. monocytogenes (21). It grew at 35 but not at 50 g/ml cadmium chloride, hence its MIC (50 g/ml) is below the 70 g/ml threshold for resistance used in previous studies (11,12,22). PCR with previously described primers (8) indicated that F8027 was negative for previously identified cadmium resistance determinants cadA1, cadA2, and cadA3 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…70% identity at the amino acid (aa) sequence level, cadA4 is noticeably divergent, exhibiting only ca. 36% identity with these other cadA determinants (11). Nonetheless, the deduced CadA encoded by cadA4 harbored all three key motifs characteristic of the CadA protein family (25): CXXC, responsible for metal binding; DKTGT, associated with ATP binding; and CXC, specifically CPC, serving as a membranebound ion transport channel (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The serotype was determined at the CDC as previously described (24) and reexamined at North Carolina State University using a multiplex PCR serotyping scheme (25), which also allowed identification of the recently recognized 4b subset IVb-v1 (Table 1) (26,27). Resistance to arsenic, cadmium, and BC was determined as described previously (28) with the modification that cadmium-resistant isolates were those growing at Ն35 g/ml cadmium chloride, reflecting our recent discovery of the association between a cadmium resistance determinant (cadA4) and growth at 35 g/ml (but not at 70 g/ml) cadmium chloride (29).…”
Section: Methodsmentioning
confidence: 99%